Advances in Cardiac Signal Processing
DOI: 10.1007/978-3-540-36675-1_5
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability

Abstract: During normal sinus rhythm, the heart rate (HR) varies from beat to beat. Heart rate variability (HRV) results from the dynamic interplay between the multiple physiologic mechanisms that regulate the instantaneous HR. It is believed that Heart Rate Variability (HRV) will become as common as pulse, blood pressure or temperature in patient charts in the near future. In the last ten years more than 2000 published articles have been written about HRV. HRV has been used as a screening tool in many disease processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
173
0
36

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(217 citation statements)
references
References 122 publications
5
173
0
36
Order By: Relevance
“…High frequency (HF: 0.15-0.40 Hz) spectral power reflects primarily parasympathetic influences, whereas low frequency power (LF: 0.04-0.15 Hz) has been shown to reflect both sympathetic and parasympathetic influences. The LFHFR reflects the relative balance between the sympathetic and parasympathetic nervous (Anonymous, 1996;Acharya et al, 2006). The results from our study implied the exposure to ambient O 3 was associated with the withdrawal of cardiac parasympathetic nervous activity (decreased HF) and prominence of sympathetic nervous activity (increased LFHFR).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…High frequency (HF: 0.15-0.40 Hz) spectral power reflects primarily parasympathetic influences, whereas low frequency power (LF: 0.04-0.15 Hz) has been shown to reflect both sympathetic and parasympathetic influences. The LFHFR reflects the relative balance between the sympathetic and parasympathetic nervous (Anonymous, 1996;Acharya et al, 2006). The results from our study implied the exposure to ambient O 3 was associated with the withdrawal of cardiac parasympathetic nervous activity (decreased HF) and prominence of sympathetic nervous activity (increased LFHFR).…”
Section: Discussionmentioning
confidence: 55%
“…(1) The elderly individuals with cardio-pulmonary diseases were chosen as the subjects in previous studies, and no study was found examining the associations in the healthy elderly individuals. It has long been demonstrated the HRV indices change with health status (cardio-pulmonary status) and drug mediations (Antelmi et al, 2004;Felber Dietrich et al, 2006;Rajendra Acharya et al, 2006), and the response of HRV to the stimulus of O 3 are suggested to be disturbed by the healthy status and drug mediations (Holguin et al, 2003;Park et al, 2005); (2) Most of the previous studies evaluated association between the O 3 concentrations monitored in the ambient stations and HRV indices measured indoors (Gold et al, 2000;Holguin et al, 2003;Liao et al, 2004;Park et al, 2005;Schwartz et al, 2005). The exposure error may occur because of the great discrepancy between indoor and outdoor O 3 concentration and the variations of indoor O 3 concentration from room to room.…”
Section: Introductionmentioning
confidence: 99%
“…Nonlinear dynamics analysis: Moreover, the nonlinear dynamics of HRV signals were also analysed. Poincare plot arranges the HRV sequences into pairs of adjacent RR intervals, in two dimensions, with two consequents (RR, RR+1) in the xand y-axes, respectively [11]. An ellipse is generated to fit the data points, from where the width (11) and the length (12) can be calculated as features.…”
Section: Frequency-domain Analysismentioning
confidence: 99%
“…Keywords: horse, heart rhythm, behaviour, training 1) Badania wykonano w ramach projektu badawczego Narodowego Centrum Nauki (N31502039).…”
Section: Praca Oryginalna Original Paperunclassified